COVID-19 vaccine confidence and reasons for vaccination among health care workers and household members. Issue 41 (29th September 2022) - Ulrich, Angela K.; Pankratz, Grace K.; Bohn, Bruno; Yendell, Stephanie; Beebe, Timothy J.; Hedberg, Craig W.; Demmer, Ryan T.
Abstract: Background: The majority of healthcare workers (HCW) in the US report being fully vaccinated against COVID-19, yet little is known about vaccine decision-making for their household members, including children. Methods: Cross-sectional survey July–August 2021 of HCW and their household members in Minnesota. Results: 94 % of eligible participants were vaccinated with the most common reasons being wanting to protect oneself, family and loved ones. Safety concerns were the most commonly reported reasons for not being vaccinated; a significantly higher proportion of unvaccinated compared to vaccinated HCW (58 % vs 12 %, p = 0.0035) and household adults (25 % vs 5 %, p = 0.03) reported prior SARS-CoV-2 infection. Nearly half of unvaccinated adults and two-thirds of unvaccinated children would be vaccinated if a vaccine mandate were in place. Conclusions: Despite high COVID-19 vaccine acceptance among HCWs, more research is required to identify and address the needs and concerns of healthcare workers who decline COVID-19 vaccination despite availability.